Simvastatin downregulates adipogenesis in 3T3-L1 preadipocytes and orbital fibroblasts from Graves' ophthalmopathy patients. Issue 9 (September 2019) - Shahida, B; Johnson, P Sahlstrand; Jain, R; Brorson, H; Åsman, P; Lantz, M; Planck, T
Abstract : Background: Smoking is a strong risk factor for the development of Graves' ophthalmopathy (GO). Immediate early genes (IEGs) are overexpressed in patients with active GO compared to healthy controls. The aim of this study was to study the effects of tobacco smoking and simvastatin on preadipocytes and orbital fibroblasts (OFs) in the adipogenic process. Methods: Cigarette smoke extract (CSE) was generated by a validated pump system. Mouse 3T3-L1 preadipocytes or OFs were exposed to 10% CSE with or without simvastatin. Gene expression was studied in preadipocytes and OFs exposed to CSE with or without simvastatin and compared to unexposed cells or cells treated with a differentiation cocktail. Results: In 3T3-L1 preadipocytes, Cyr61, Ptgs2, Egr1 and Zfp36 expression levels were two-fold higher in cells exposed to CSE than in unexposed cells. Simvastatin downregulated the expression of these genes (1.6-fold, 5.5-fold, 3.3-fold, 1.4-fold, respectively). CSE alone could not stimulate preadipocytes to differentiate. Scd1, Ppar-γ and adipogenesis were downregulated in simvastatin-treated preadipocytes compared to nontreated preadipocytes 18-, 35- and 1.7-fold, respectively. In OFs, similar effects of CSE were seen on the expression of CYR61 (1.4-fold) and PTGS2 (3-fold). Simvastatin downregulated adipogenesis, PPAR-γ (2-fold) and SCD (27-fold) expression in OFs. Conclusion: CSE upregulated early adipogenic genes in both mouse 3T3-L1 preadipocytes and human OFs but did not by itself induce adipogenesis. Simvastatin inhibited the expression of both early and late adipogenic genes and adipogenesis in preadipocytes and human OFs. The effect of simvastatin should be investigated in a clinical trial of patients with GO.